The effectiveness of imaging modalities in clinical staging of localized prostatic carcinoma - (:unkn) unknown (Kluwer Academic Publishers, 1996)
Findings on transrectal ultrasonography (TRUS), computerized tomography (CT), and magnetic resonance imaging (MRI) in local staging of prostatic carcinoma (PCa) were compared with the final pathological staging in 30 patients who underwent radical prostatectomy. We found TRUS and MRI to have the same accuracy rate (53%) in local staging, whereas CT revealed a lower accuracy rate with 47%. TRUS revealed the highest accuracy rate in detecting seminal vesicle invasion with 70%, and MRI in invasion of periprostatic tissue with 67%. Although it revealed similar efficiency as MRI, TRUS should be considered as the first line modality in local staging of PCa in light of its relatively high accuracy rate, cost effectiveness and ease in performance.